PENGARUH KESESUAIAN BAHAN AJAR ELEKTRONIK TERHADAP MOTIVASI BELAJAR SISWA DI KELAS TINGGI SD: TINJAUAN PUSTAKA - Iis Maesaroh; Nurfalah, Siti; Nursyamsiah, Siti; Dewi, Ratna Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The historical foundation of education in Indonesia is a crucial element in understanding the development and dynamics of the national education system. This article aims to review the literature related to the history of education in Indonesia, covering the evolution of thought, policies, and practices over time. Using a systematic literature review approach, the article provides an in-depth analysis of theories, social contexts, and political influences that have shaped education in Indonesia. Emphasis is placed on how the education system has evolved to address local and global challenges.